INCRASING OF OXYGEN CONSUMPTION IN WOMEN BETWEEN 30 TO 39 YEARS OLD IN CONCÓRDIA CITY THROUGH WALK OF 1,600 METERS (Fiep Bulletin - online, 2014)
The maximum consumption of oxygen is considered as the better indicators of sum health of the human being. Much more the consumption of the oxygen, better the sum health of the person. Among the aerobic modalities the walk is the modality more indicated to sedentary people. Currently, according to doctor orientations, the walks could be realized with a moderated intensity and duration of 30 minutes three times a week. The results of the research, realized by us, showed that the walks with these orientations do not improve VO2max of the people with the medium age. Other research that we realized showed that the realizations in alternate days of the walks of 1,600 meters com elevate intensity improve VO2max of aged people. The purpose of the research was to verify if the walk of four  laps of the athletics track with the speed with the maximum intensity each one could, improve VO2max of medium age people. The sample of the research was composed by 15 voluntaries female healthy people from 30 to 39 years old in Concórdia city - SC. The people of the sample did three times a week during three weeks in a row to walks traveling around four laps of the athletics track with the speed "the most rapid each one could". Previous and subsequent weeks of the walks, through Rockport Test, I was determinate VO2max of those. Previous and subsequent weeks of the walks, through Rockport Test, It was determinate VO2max of those. The results acquired showed that the walks realized three times a week during four weeks in a row in a distance of 1,600 meters with a speed faster that each one could VO2max of the female healthy people from 30 to 39 years old, in average, of 5,6% (p < 0,01). Conclusion: the walking of four laps of the athletics track with the speed "the most rapid each one could" three times a week, could be used to improve VO2max of the female healthy people from 30 to 39 years old.
Keywords: maximum consumption of oxygen; physic activity; walking